Intense aqueous alteration on C-type asteroids: Perspectives from giant fine-grained micrometeorites. (15th January 2019) - Suttle, M.D.; Folco, L.; Genge, M.J.; Russell, S.S.; Najorka, J.; van Ginneken, M.
Abstract: This study explores the petrology of five giant (>400 μm) hydrated fine-grained micrometeorites from the Transantarctic Mountain (TAM) micrometeorite collection. For the first time, the extent and mechanisms of aqueous alteration in unmelted cosmic dust are evaluated and quantified. We use a range of criteria, previously defined for use on hydrated chondrites, including phyllosilicate fraction, matrix geochemistry and micro textures. Collectively, these micrometeorites represent ∼2.22 mm 2 of intensely altered hydrated chondritic matrix (with petrologic subtypes of <1.2 in the scheme of Howard et al. (2015)) and reveal a range of alteration styles. Two particles are found to contain pseudomorphic chondrules with thick fine-grained rims, while another micrometeorite contains several aqueously altered CAIs. Their outlines range from well-defined to indistinct, demonstrating that the advanced stages of aqueous alteration progressively remove evidence of coarse-grained components. The remaining two micrometeorites entirely lack coarse-grained components but are similarly altered. Thus, the combined chondrule-to-matrix ratio among these giant micrometeorites is extremely low (6.45 area%), and significantly below the average ratio found in typical CM or CR chondrites (∼20%, Weisberg et al., 2006). Our findings are consistent with previous analyses from smaller Antarctic micrometeorites, which suggest that chondrules (and CAIs) derived from hydrated carbonaceous chondrite parent bodies are underrepresented among the micrometeorite flux, even when considering contributions from coarse-grained micrometeorites. Therefore, to explain the relative paucity of anhydrous material, we propose that the flux of fine-grained micrometeorites is primarily derived from intensely aqueously altered, primitive C-type asteroids, which have lost the majority of their refractory coarse-grained components by replacement with secondary phyllosilicate minerals.